PENGARUH PENGEMBANGAN KARIR, FASILITAS KERJA, KOMITMEN PROFESI DAN PENGAWASAN KERJA TERHADAP KINERJAPEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA TEBING TINGGI - Rahmad syah (Jurnal Prodi Fakultas Ekonomi-UISU, 2020)
The problem in this research is how the influence of career development, work facilities, professional commitment and supervision of work partially or simultaneously on the performance of employees in the Tebing Tinggi Pratama Tax Office The research objective: To determine the effect of career development, work facilities, professional commitment and work supervision partially and simultaneously on the performance of employees in the Primary Tax Office Tebing Tinggi. The hypothesis proposed is: There is the influence of career development, work facilities, professional commitment, partial supervision and jointly on the performance of employees at the Primary Tax Office Tebing Tinggi. The study was conducted at the Tebing Tinggi Pratama Tax Service Office Jalan Sutoyo Number 32 Rambung Tebing Tinggi., With a population of 82 people, and a study sample of 82 people. Based on the results of the analysis, there is a significant influence between career development on the performance of the Pratama Tebing Tinggi Tax Office employee, because according to the results of the t count t-table analysis (1.895 1.67) at n = 82 with a significance level of 95%. There is a significant influence between work facilities on the performance of the Primary Tax Office employees of Tebing Tinggi, the results of t count analysis t-table (1,874 1.67) at n = 82 with a level of significance of 95%. There is a significant influence between professional commitment to the performance of the Primary Tax Service Office Tebing Tinggi, because according to the results of the analysis t count t-table (2.074 1.67) at n = 82 with a significance level of 95%. There is a significant influence between the supervision of the performance of the Pratama Tebing Tinggi Tax Office employee, because according to the results of the t-count analysis t-table (2.493 1.67) at n = 82 with a significance level of 95%. Together (multiple) there is a positive and significant influence on career development, work facilities, professional commitment and supervision of the performance of employees of the High Pratama Tax Service Office, because the F test results obtained F-count F table (12,305 2,48) . Thus the hypothesis proposed is accepted by the truth.